Islamic Management Education as Pivotal Tool to Reduce Inequality of Online Learning During The Covid-19 Pandemic in Indonesian Higher Education - Sulistyorini, Sulistyorini (JURNAL AL-TANZIM, 2023)
Online-based education due to the COVID-19 pandemic has created class inequality between students from the lower middle class/poor economic group and students from the upper class/elite financial group. This article aims to fill existing research gaps regarding class inequality during the pandemic, creating gaps in student experience and learning outcomes. The approach is qualitatively collected using observation, interview, and documentation techniques. The results are analyzed, interpreted, and verified on the MaxQDA application. This study's findings are that in its implementation, online education creates inequality related to learning support tools: cell phones and laptops, quotas, and internet networks. Then, family background factors are also the cause of inequality, especially concerning work or income, parents' educational background, and the area where they live. As a result, the disparity in online education impacts student learning outcomes that decline and soar parental spending to meet additional needs to support learning activities. Thus, rapid response from universities is needed to immediately overcome this inequality because the demands for technological education, on the other hand, also create gaps in learning.